1997
DOI: 10.1093/jnci/89.14.1027
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Small-Cell Lung Cancer Cells by an Antisense Oligodeoxynucleotide Targeting the Bcl-2 Coding Sequence

Abstract: We have identified a novel antisense ODN sequence (ODN 2009) that effectively reduces the viability of small-cell lung cancer cells by reducing Bcl-2 levels and facilitating apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
1

Year Published

1998
1998
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(90 citation statements)
references
References 25 publications
3
86
1
Order By: Relevance
“…Once the optimal growth conditions have been established for each cell line. the WST-1 viabilitv assav provides reproducible results which correlate well with the actual number of X iable cells determined by propidium iodide exclusion (Ziegler et al 1997 Germanv) was added per well and allowed to react for 3-5 h at 37"C. Absorbance at 450 nm was measured by use of an enzx-melinked immunosorbent assav reader (2550 EIA reader. Bio Rad Laboratories.…”
Section: Measurement Of Cell Viabilitymentioning
confidence: 73%
See 3 more Smart Citations
“…Once the optimal growth conditions have been established for each cell line. the WST-1 viabilitv assav provides reproducible results which correlate well with the actual number of X iable cells determined by propidium iodide exclusion (Ziegler et al 1997 Germanv) was added per well and allowed to react for 3-5 h at 37"C. Absorbance at 450 nm was measured by use of an enzx-melinked immunosorbent assav reader (2550 EIA reader. Bio Rad Laboratories.…”
Section: Measurement Of Cell Viabilitymentioning
confidence: 73%
“…Recently. we has-e identified an antisense sequence (ODN 2009) targeting the bcl-2 coding region that effectixelv downregulated bcl-2 expression and induced apoptosis in SCLC cells (Ziegler et al 1997). In the present study.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…1,2 Because anti-apoptotic proteins, bcl-2 and bcl-xL, are often enhanced in various cancers, where they may play a pivotal role in tumor initiation and progression, 3,4 bcl-2 and bcl-xL genes were suggested to be targets for cancer gene therapy. Administrations of bcl-2 and bcl-xL antisense oligonucleotides promoted apoptosis and inhibited cell growth in brest carcinoma cells 5 and small-cell lung cancer cells, 6 in which bcl-2 or bcl-xL was detectable. In our previous report, 7 we examined the effects of in vivo electroporetic transfer of a bcl-2 antisense oluigonucleotide phosphorothioate on rat hepatocarcinogenesis, and showed that bcl-2 antisense oligonucleotide inhibited expression of bcl-2 mRNA and the occurrence and growth of rat hepatocellular carcinoma induced by NNM.…”
Section: Introductionmentioning
confidence: 97%